Conhecimento de profissionais brasileiros sobre transtorno do desenvolvimento da coordenação: survey com pediatras, terapeutas ocupacionais, fisioterapeutas e professores - Lilian Viviane Barbosa (2023)
Introduction: Developmental Coordination Disorder (DCD) is a common health condition in childhood, with an international prevalence estimated of 5% to 6% in school-aged children and prevalence rates in Brazilian studies ranging from 4.3% to 47,2%. However, there is evidence that the disorder is still little known by professionals in the areas of Health and Education, resulting in delays in diagnosis and access to treatment. So far, no study has investigated the knowledge of Brazilian professionals about DCD. Objective: To verify whether Brazilian teachers, pediatricians, occupational therapists and physiotherapists who work with children and teenagers aged 6 to 17 and 11 months are familiar with DCD. Method: Descriptive, cross-sectional Survey with Brazilian professionals using an on-line questionnaire. The questionnaire was developed based on published studies and submitted to expert review, to adjust to local context. Results: A total of 803 Brazilian professionals answered the questionnaire, including 547 teachers, 146 occupational therapists, 57 physiotherapists and 53 pediatricians. DCD is among the least known childhood and adolescence health conditions by practitioners, with 57% of participants having some degree of familiarity with the condition. The motor characteristics of the disorder are best recognized, compared to non-motor characteristics, in all professional groups. In general, healthcare professionals claim to have more knowledge about DCD (72.6%) than teachers (49.1%). Among the health professionals, occupational therapists were the ones who claimed to know more or have heard about the disorder (82.2%), followed by 73.7% of physiotherapists, and 45.3% of pediatricians. Few health professionals have raised the possibility of considering the diagnosis of DCD for a child and only 17% of the pediatricians have made a diagnosis of DCD. Conclusion: Given the relevance of the professionals participating in this study to the process of identification and diagnosis of DCD, resulting in only 57% of them knowing or having heard about DCD shows that more efforts are needed to increase the familiarity and knowledge about the disorder. Implementation of knowledge translation strategies for professionals and society in general is essential to increase the awareness of DCD, from its definition, diagnosis, and evaluation to evidence-based intervention strategies.